Combination of dihydromyricetin and ondansetron strengthens antiproliferative efficiency of adriamycin in K562/ADR through downregulation of SORCIN: A new strategy of inhibiting P‐glycoprotein. Issue 4 (31st August 2018) - Sun, Yaoting; Liu, Wei; Wang, Changyuan; Meng, Qiang; Liu, Zhihao; Huo, Xiaokui; Yang, Xiaobo; Sun, Pengyuan; Sun, Huijun; Ma, Xiaodong; Peng, Jinyong; Liu, Kexin
Abstract: Though the advancement of chemotherapy drugs alleviates the progress of cancer, long‐term therapy with anticancer agents gradually leads to acquired multidrug resistance (MDR), which limits the survival outcomes in patients. It was shown that dihydromyricetin (DMY) could partly reverse MDR by suppressing P‐glycoprotein (P‐gp) and soluble resistance‐related calcium‐binding protein (SORCIN) independently. To reverse MDR more effectively, a new strategy was raised, that is, circumventing MDR by the coadministration of DMY and ondansetron (OND), a common antiemetic drug, during cancer chemotherapy. Meanwhile, the interior relation between P‐gp and SORCIN was also revealed. The combination of DMY and OND strongly enhanced antiproliferative efficiency of adriamycin (ADR) because of the increasing accumulation of ADR in K562/ADR‐resistant cell line. DMY could downregulate the expression of SORCIN and P‐gp via the ERK/Akt pathways, whereas OND could not. In addition, it was proved that SORCIN suppressed ERK and Akt to inhibit P‐gp by the silence of SORCIN, however, not vice versa. Finally, the combination of DMY, OND, and ADR led to G2/M cell cycle arrest and apoptosis via resuming P53 function and restraining relevant proteins expression. These fundamental findings provided a promising approach for further treatment of MDR. Abstract : Soluble resistance‐related calcium‐binding protein suppressed expression of P‐glycoprotein via ERK/Akt signaling pathways. Coadministration of dihydromyricetin and ondansetron could strongly enhance the antiproliferative efficiency of adriamycin (ADR) by promoting ADR‐induced G2/M cell cycle arrest and apoptosis.